Pengaruh Strategi Resource-Based terhadap Keunggulan Bersaing yang Dimediasi oleh Orientasi Kewirausahaan (Studi pada Usaha Kecil Menengah Sasirangan Kota Banjarmasin) - Putra, Defin Shahrial; Djazuli, Atim (Jurnal Aplikasi Manajemen, 2013)
This research aims to examine and analyze the effects of resource-based strategy towards the orientation of entrepreneurship and small and medium enterprises competitive advantage, as well as test and analyze the effect of entrepreneurial orientation on the competitive advantage of small to medium-sized sasirangan. As well as test and analyze the effect of entrepreneurial orientation on the competitive advantage of small to medium-sized sasirangan. The study also tested and analyzed the effect of entrepreneurial orientation on indirect resource-based strategy of medium-small business competitive advantage sasirangan. This research sample of 37 medium-small business sasirangan in the city of Banjarmasin taken with Census and sampling methods were analyzed by using the method of Partial Least Square (PLS). The findings in this study are the effects of resource-based strategy in the entrepreneurial orientation variables will be reinforced to create sustainable competitive advantage on small and medium enterprises. Entrepreneurial orientation's influence and the presence of small and medium enterprises competitive advantage sasirangan. The findings in this study, there is an indirect effect of entrepreneurial orientation on resource-based strategy of medium-small business competitive advantage sasirangan in the city of Banjarmasin.